A STUDY ON THE MAINTENANCE MANAGEMENT SYSTEMS OF EASTERN SAMAR NATIONAL COMPREHENSIVE HIGH SCHOOL BUILDINGS-BASIS FOR THE DEVELOPMENT OF A HOLISTIC MAINTENANCE MANAGEMENT SYSTEM - Alipio Antonio B. Añano Jr; Ma. Mercia G. Corado; Felinda T. Jamer (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
The purpose of this study are the following: to identify the present maintenance management systems of the school buildings of Eastern Samar National Comprehensive High School (ESNCHS), to describe the current conditions of the school buildings of ESNCHS and to design a holistic framework that will help improve the maintenance management systems. This research employed the qualitative method that is rooted in the phenomenological paradigm. Also, this research employed the case study research design. This design is appropriate if a study intends to learn more specifically, contextually, in-depth information on a particular real-world topic, a case study is a suitable research design (McCombes, 2019) Every institution must follow strict and legal guidelines in terms of spending or funding for its physical plant and facilities. In the case of ESNCHS, its budget and fund management is saddled in the revised guidelines for the Implementation of the Basic Educational Facilities Fund (BEEF) Manual of DepEd. contributed to the efficient management. Thus, the efficiency of the budget and fund management in the maintenance of its school building. Moreover, having extra source of fund, such as other income-generating funds of the school also help augment the expenses for the schools’ school building maintenance